Differential Nitrogen Nutrition Modifies Polyamines and the Amino-Acid Profile of Sweet Pepper Under Salinity Stress - Piñero, M. C.; Porras, Manuel E.; López-Marín, Josefa; Sánchez-Guerrero, Mari C.; Medrano, Evangelina; Lorenzo, Pilar; del Amor, Francisco M. (Frontiers in Plant Science, 2019)
The horticultural industry demands high-quality resources to achieve excellence in yield and optimal revenues. Nitrogen is a pivotal nutrient to accomplish these goals for plant growth and product quality. However, competition for water in semi-arid regions can force the use of brackish waters, which can impair N uptake. The lower N uptake can be due to several reasons, such as an antagonism between ions, an absence of ATP, and/or alteration of N metabolism. The effect of supplying N as NO3- alone or in combination with NH4+, coupled with low or high salinity (8 or 20 mM NaCl), has been studied in sweet pepper fruits (Capsicum annuum L. cv. Melchor). The application of NH4+ at high salinity affected chromatic parameters (a*, b*, and C*), while chlorophyll a and b levels declined and β-carotene increased. The concentrations of P, K, Ca, Mg, and Cu were reduced in the fruits of plants irrigated with NH4+. The concentration of Na was only reduced when NH4+ was supplied. Likewise, the concentration of total phenolics was also reduced at high salinity. However, total protein was unaffected. The amino acid profile was altered by the supply of NH4+, which reduced the concentrations of histidine and phenylalanine. Moreover, the concentrations of putrescine and cadaverine were increased by NH4+ at high salinity, whereas that of cadaverine was reduced by NH4+ at low salinity. The observed changes in fruit quality triggered by salinity, under the conditions of this study, should be borne in mind for this crop with regard to the envisaged palliative effect of the supply of N-NH4+.